Conceptual provisions of the transformation of the national energy system of Ukraine in the context of the European Green Deal - Pahlevanzade, Alborz; Pahlevanzade, Alireza; Trushkina, Nataliia; Maslennikov, Yevgen (My University, 2021)
This article is aimed at the scientific and methodological substantiation of conceptual provisions for the transformation of the national energy system of Ukraine through the formation of eco-energy clusters. The article analyses international reports on the development of green energy in different countries. An analysis of the dynamics of energy consumption in Ukraine on the basis of renewable sources for 2007–2019 is performed. An algorithm for making a management decision on the transition to renewable energy sources is proposed. In order to transform the national energy system, a conceptual approach to the formation of an eco-energy cluster as an element of innovation infrastructure based on smart specialization is substantiated. It is proven that this structure should be in the form of the partnership of energy companies, business structures, research institutions,higher education institutions, institutions of logistics, energy and innovation infrastructure, and government agencies. This, in turn, will provide a synergistic effect (economic, environmental, social) by improving a number of existing legislations on alternative energy sources, which would increase the economic efficiency of their production, such as: the development of investment projects to attract additional investments in this industry; state guarantees to producers of “clean” energy for its purchase at fixed tariffs; ensuring the level of energy security of Ukraine through the modernization of the network of existing power plants to increase the level of their reliability and uninterrupted operation; the reduction of greenhouse gas emissions from the combustion of traditional fuels.
Trushkina, N. Conceptual provisions of the transformation of the national energy system of Ukraine in the context of the European Green Deal / A. Pahlevanzade, N. Trushkina, A. Pahlevanzade, Y. Maslennikov // Polityka Energetyczna – Energy Policy Journal. – 2021. – Vol. 24, Issue 4. – P. 121-138.
Keywords: state energy policy; national energy system; renewable energy; eco-energy cluster; green technologies; green economics